An Ethnographic Study of Abacus Use Among Visually Impaired Individuals in Solving Addition and Subtraction Problems - Siti Mutmainah; Mega Suliani (Jurnal Pendidikan Matematika Universitas Lampung, 2026)
This study explores the use of the abacus (sempoa) as a tactile learning tool by visually impaired elementary school students in solving addition and subtraction problems. Employing a qualitative case study approach with an ethnographic orientation, this research involved three visually impaired elementary school students selected through purposive sampling. The participants were chosen based on three criteria: having visual impairment, possessing prior experience in using the abacus, and being actively involved in learning addition and subtraction operations.  Data were collected through participant observation, in-depth interviews, and analysis of modified abacus artifacts. The findings reveal that the abacus functions as a “tactile cognitive map,” enabling students to bridge abstract mathematical concepts and physical reality. Students employed a consistent two-handed technique, where the left hand guided place value and the right hand executed bead movements. Addition involved moving beads toward the center bar, whereas subtraction involved moving them away, reflecting complex mental restructuring during “carrying” and “borrowing” tasks. The effectiveness of abacus use depended on fingertip sensitivity, procedural consistency, and working memory. Ultimately, the abacus supported students’ independence, confidence, and participation in inclusive mathematics learning.